PENGARUH DIGITAL MARKETING TRAINING TERHADAP KEMANDIRIAN DAN ENTREPRENEURSHIP KNOWLEDGE CURIOSITY DIKALANGAN MAHASISWA UNWAHA - Rohmah, Nailis Sa'idatur; Ashlihah, Ashlihah (JoEMS (Journal of Education and Management Studies), 2021)
This study aims to determine whether digital marketing training affects the independence and entrepreneurial knowledge curiosity of UNWAHA students. In addition, between the independent variable and the dependent variable is there a relationship between the two variables. The analytical method used in this study is a quantitative descriptive analysis method with a simple linear regression test. The device or tool used is a test that uses the IBM SPSS version 23 instrument. The results show that digital marketing training on independence and Entrepreneurship knowledge curiosity has no effect/no relationship between variable X (digital marketing training) on ​​variable Y1 (independence) and variable Y2 (Entrepreneurship knowledge curiosity). The size of the correlation/relationship (R) value is 0.110. From the output, the coefficient of determination (R Square) is 0.012. which implies that the effect of the independent variable X (Digital Marketing Training) on ​​the dependent variable Y1 (Independence) is 1.2%. The size of the correlation/relationship (R) value is 0.188. From the output, the determinant coefficient (R Square) is 0.035 which implies that the effect of the independent variable X (digital marketing training) on ​​the dependent variable Y2 (Entrepreneurship knowledge curiosity) is 3.5 %.